Evaluation of the presence of Aspergillus spp in feed for livestock in times of drought in Aguachica - Colombia (@limentech, Ciencia y Tecnología Alimentaria, 2024)
The fundamental aspect in the livestock of Cesar is based on having cattle with good health and quality of life. In summer the pastures supplied have low levels of proteins and vitamins, so alternatives are sought to produce supplementary foods such as concentrates, silos and / or feed. Supplements allow to maintain the required levels of production, but there is a risk that there is the presence of some molds that affect the quality of milk. In the department of Cesar, Colombia, there have been no studies that delve into knowing the reasons for the presence of this type of microorganism in milk. The purpose of this research was to evaluate the possible presence of mold Aspergillus spp in different types of feed for dairy cattle in times of drought in Aguachica - Cesar-Colombia. In this research, a selection of 40 feeds used in the different dairy herds was carried out to identify the presumptive presence of the mold Aspergillus spp. The feed was selected manually and transported in refrigerated cellars to the dairy plant in Aguachica – Cesar. It was found that the possible species that can be found frequently of the genus Aspergillus are A. flavus, A. niger, A. parasiticum, A. restrictus, A. fumigatus, A. candidus. The presence of these microorganisms is directly related to the type of storage of the feed.
Keywords: Aflatoxins; anoxygenic; Aspergillus spp; feed; Silage